“”Satisfacción del usuario adulto y su relación con la atención de las enfermeras en el servicio de hospitalización de medicina del hospital LL – 1 Minsa – Tarapoto Julio – Octubre 2,009 - Parillo Condori, Lourdes Gabriela (2010)
"This research is a descriptive study correlates!, prospective, transverse cut!," performed with ei objective determine ta relation existing between the adult user satisfaction - and la· "atefl'.;.." off ~ Jas nurses in hospital of medicine from the Hospial 11-1 MINSA Tarapoto ~icio. The study population consisted of 103 hospitalized adults - Jutio· to OctubTe det 2009 that formed the grup·o-of study. A survey was applied for data collection by .se. structured · 40 questions which were processed through the statistical package SPSS 11th, to determine fa relationship that exists between fa ta tas (p 0.05 s) nurses care and adult user satisfaction, reaching the following conciusiones: 1. the adult user satisfaction is average ({X = 24.04 pts}, with a range of 17-30 pts.) 2 l.a nursing care perC1btda by fos users is Regular (X: 74.96 pts), with a rank 64:. 1 ff-piS. 3. ...